Gaining credibility and enhancing economic growth through regional integration: The case for EU membership of Eastern Europe - Daniel Piazolo (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
Trade between Eastern and Western Europe has increased considerably in the last years. Given this market-induced development, why should it be necessary to advance institutional integration? This paper argues that Central and Eastern European countries (CEECs) can potentially enhance the credibility of their governments' policies through institutional integration with the EU. The paper discusses the credibility problems faced by the CEECs and shows how EU membership will enhance the institutional setting and the governments' credibility. Based on regression results between an indicator of institutional change and key macroeconomic variables, an estimate of the potential impact of the CEECs' accession to the EU institutional framework on growth in the CEECs is derived.
Keywords: F15; P47; 330; Institutional change; institutional integration; transition; credibility; EU enlargement; Institutioneller Wandel; Systemtransformation; Glaubwürdigkeit; EU-Erweiterung; Wirtschaftswachstum; Theorie; Osteuropa